The Capture of Jerusalem by the Muslims in 634 - SYVÄNNE, Ilkka (Historia i Świat, 2019)
The aim of this article is to show that there is an alternative way to reconstruct the Muslim conquest of Roman Levant, which is actually militarily more plausible than the current consensus view among historians.